Efektivitas Kampanye Cegah Penggunaan Narkoba Badan Narkotika Nasional (BNN) di Media Sosial Instagram Terhadap Sikap Pelajar SMA PGRI 2 Denpasar - Adhyatmanta, Made; Alit Suryawati, I Gusti Agung; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium; Vol 1 No 1 (2019), 2019)
ABSTRACT The University of Indonesia and the National Narcotics Research Center conducted a research showing 27.32 percent of users in Indonesia were students. In Bali, 16-19 year olds involved in drug cases increased 73 percent. The object of this research is SMA PGRI 2 Denpasar. From the results of the BNN urine test, there were 2 students suspected of using illegal drugs. The method of this research is quantitative and uses descriptive statistics in analyzing data. The purpose of this study was to determine the effectiveness of the campaign to prevent drug use from the City of Denpasar on the social media Instagram on the attitude of high school students PGRI 2 Denpasar. The results of this research are quite effective, the results of the respondents' data processing do not all follow the Instagram account of BNN Kota Denpasar, but most know the Instagram account of BNN Kota Denpasar. Key words: Campaigns, National Narcotics Agency (BNN) Denpasar, Instagram.